Increased Consumption of Unsaturated Fatty Acids Improves Body Composition in a Hypercholesterolemic Chinese Population - Haldar, Sumanto; Ponnalagu, Shalini; Osman, Farhana; Tay, Shia Lyn; Wong, Long Hui; Jiang, Yuan Rong; Leow, Melvin Khee Shing; Henry, Christiani Jeyakumar (Frontiers in Nutrition, 2022)
While increase in fat intake and the resulting excesses calorie intake are implicated in weight gain, different fat types exert variable effects on body composition, with unsaturated fats showing favourable effects on body composition in Western populations. Whether and to what extent these associations apply to Asian populations have not been established. We investigated effects of two separate Asian based oil blends, rich in unsaturated fats, made from refined rice bran, sesame and flax seed oils, in comparison with refined olive oil, on body composition using dual energy X-ray absorptiometry (DXA), from an 8-week, parallel design, randomized trial in 66 males (58.7 ± 5.71yr old, 23.0 ± 2.38 kg/m2) and 69 postmenopausal females (59.1 ± 5.34 yr old, 21.7 ± 2.52 kg/m2), with borderline hypercholesterolemia. Despite increases in mean daily intakes of total energy (~ +400 kcal/d, F and ~ +240 kcal/d, M), as well as increases in % calories from fats and proteins and a decrease in % calories from carbohydrates during the dietary intervention period, there were no significant changes in total body fat mass in both genders, all treatment groups. While total body weight increased slightly (0.36 ± 0.12 kg, p=0.005) in females during intervention, this was mainly due to gain in lean mass (0.38 ± 0.081 kg, p<0.0001). Correspondingly, there were reductions in total body fat (%), android fat (%) and gynoid fat (%) in females. No significant differences between the 3 intervention oil types were found in any of the measured parameters, in either genders. Increasing relative intakes of unsaturated fats may prevent fat mass gain and circumvent muscle mass loss associated with menopause in older Asian women. Longer term studies are needed to confirm findings. This study had been registered on clinicaltrials.gov (Identifier No. NCT03964857, https://www.clinicaltrials.gov/ct2/show/NCT03964857).